The effect of structural breaks on the Engle-Granger test for cointegration - Noriega, Antonio E.; Ventosa Santaulária, Daniel (Estudios Económicos de El Colegio de México, 2012)
This paper extends Gonzalo and Lee’s (1998) results by studying the asymptotic and finite sample behavior of the Engle-Granger test for cointegration, under misspecification of the trend function in the form of neglected structural breaks. We allow breaks in level and slope of trend in both dependent and explanatory variables. We also allow these processes to interact with I(1) processes without breaks. In some cases, breaks bias the EG test towards both rejecting a true cointegration relation, and not rejecting a non-existent one. Using real data, we present an empirical illustration of the theoretical results.